Analysis of PT PLN's Innovative Strategy in Supporting Electric Vehicles in Indonesia - Prakoso, Iwan Catur; Anggarani, Ari (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Global transformation towards sustainable mobility, the electric vehicle (EV) industry plays an important role in creating a cleaner and environmentally friendly future with the journey towards sustainable mobility, PT PLN (Persero) plays an important role in supporting the electric vehicle ecosystem in Indonesia. With more than a thousand Public Electric Vehicle Charging Stations (SPKLU) operating by the end of 2023, PT PLN confirms its commitment to accelerate the transition to clean mobility. However, technical challenges, change management, and organizational culture are obstacles that must be overcome. This research method uses a qualitative approach to understand PT PLN's strategy in supporting the electric vehicle ecosystem in Indonesia. PT PLN's strategy in supporting clean mobility includes infrastructure development, strategic partnerships, home charging installation initiatives, and the application of digital technology. Through holistic analysis, it highlights the importance of effective change management and an inclusive organizational culture. The results of this research provide insight into best practices in supporting the electric vehicle ecosystem and provide input for designing more effective policies. By continuing to strengthen infrastructure, develop partnerships, empower communities, technological innovation and good change management, PT PLN can strengthen its role as a leader in clean mobility and contribute to global sustainable development goals.